Content Analysis of First Grade English Student's Textbook - Alawiyah, Farihatul; Ambarwati, Evi Karlina (Jurnal Basicedu, 2023)
Textbooks are one of the supports in teaching-learning process used as learning media in EYL classroom. As a teaching material, of course, it needs to be in accordance with the standards for textbooks writing so that it is suitable for use. But in reality, there areÂ  still textbooks that are not in accordance with these standards. The aim of this research is to determine the content feasibility of textbook based on Badan Standar Nasional Pendidikan (BSNP). The research subject was an English textbooks entitled "My Next Words Grade 1 - Student's Book for Elementary School. This study used qualitative reseacrh design with contents analysis techniques. The result of this research found that from all aspects analyzed, including the material, linguistic, material presentation, and graphical aspects, indicates that this textbook to be in accordance with BSNP criteria in good category. Thus, the textbook was suitable for used by teachers and students as teaching materials.